(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
The adults and nymphs ofrugose spiralling whitefly, Aleurodicusrugioperculatuswere collected from ten different host crops (coconut, banana, arecanut, bamboo palm, Syzygium sp. maize, guava, custard apple, sapota, karanja) during 2021-2023. The fungal isolation from adults and nymphs was carried out through plating technique and obtained colonies were pure cultured for identification. The results revealed that, Aspergillus spp. and Penicilliumspp.. were found common in adults and nymphs of A. rugioperculatuscollected on seven host crops (coconut, banana, arecanut, bamboo palm, guava, custard apple, and sapota). The fungi were identified based on conidia and conidiophore structure. The role of fungus in association with A. rugioperculatus is assumed to be symbiotic, where fungus would help in digestion of cellulose and provides nutritional support.